2021
DOI: 10.23925/2179-3565.2021v12i1p170-187
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Firm Performance: Evidence From Listed Firms of Pakistan

Abstract: This study aims to find the influence of corporate governance on firm performance for the listed non-financial firms on the Pakistan Stock Exchange (PSX) for the period 2005-15.  The article has measured corporate governance by the large boards with more independent directors, independence of audit committee, ownership concentration, non-existence ofCEOduality, and presence of foreign and institutional investors. To address this endogenous nature of institutional ownership and performance in this study we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…It has been demonstrated that various forms of governance can have an effect on social duties. This assertion is supported by Ali et al (2021) , who cite several studies which demonstrate that the board of directors has the greatest influence on the performance of CSR programs. The capacity of an organization to effectively manage its relationships with its many stakeholders has a substantial bearing on the success of the organization.…”
Section: Hypotheses Developmentmentioning
confidence: 86%
See 1 more Smart Citation
“…It has been demonstrated that various forms of governance can have an effect on social duties. This assertion is supported by Ali et al (2021) , who cite several studies which demonstrate that the board of directors has the greatest influence on the performance of CSR programs. The capacity of an organization to effectively manage its relationships with its many stakeholders has a substantial bearing on the success of the organization.…”
Section: Hypotheses Developmentmentioning
confidence: 86%
“…In place of concentrating on a select few indicators, several research opt to make use of a composite measure of corporate governance. Ali et al (2021) created an indicator of governance in their respective studies (G-index). Because there has been a significant amount of research conducted on this topic, we will begin by conducting a literature review on the pertinent topics and then zeroing in on the connection that exists between corporate governance metrics and the level of success achieved by companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore they are less concernced with dividend cuts and omissions rather they are more concern with long term survival of the firm. The results are parallel to Ali et al (2021).…”
Section: Ownership Structure and Dividend Smoothingmentioning
confidence: 95%
“…Research by Bekiaris (2021) stated that foreign directors could lead to less effective monitors. Foreign directors may also be less effective on corporate boards due to their physical, cultural, and language differences (Ali et al, 2021). On the other hand, foreign directors possess the foreign experience to improve firm performance (Ali et al, 2021).…”
Section: Number Of Foreign Directors (Nofd)mentioning
confidence: 99%
“…Foreign directors may also be less effective on corporate boards due to their physical, cultural, and language differences (Ali et al, 2021). On the other hand, foreign directors possess the foreign experience to improve firm performance (Ali et al, 2021). All the empirical results on the impact of foreign directors' appointments on a firm's performance were inconsistent.…”
Section: Number Of Foreign Directors (Nofd)mentioning
confidence: 99%